DC-Obesity: a new model for estimating differential lifetime costs of overweight and obesity by socioeconomic status - Sonntag, Diana; Jarczok, Marc N.; Ali, Shehzad (Obesity, 2017)
Objective: The aim of this study was to quantify the magnitude of lifetime costs of overweight and obesity by socioeconomic status (SES). Methods: Differential Costs (DC)-Obesity is a new model that uses time-to-event simulation and the Markov modeling approach to compare lifetime excess costs of overweight and obesity among individuals with low, middle, and high SES. SES was measured by a multidimensional aggregated index based on level of education, occupational class, and income by using longitudinal data of the German Socioeconomic Panel (SOEP). Random-effects meta-analysis was applied to combine estimates of (in)direct costs of overweight and obesity. Results: DC-Obesity brings attention to opposite socioeconomic gradients in lifetime costs due to obesity compared to overweight. Compared to individuals with obesity and high SES, individuals with obesity and low SES had lifetime excess costs that were two times higher (€8,526). In contrast, these costs were 20% higher in groups with overweight and high SES than in groups with overweight and low SES (€2,711). Conclusions: The results of this study indicate that SES may play a pivotal role in designing cost-effective and sustainable interventions to prevent and treat overweight and obesity. DC-Obesity may help public policy planners to make informed decisions about obesity programs targeted at vulnerable SES groups.